PENGARUH IMPLEMENTASI KEBIJAKAN DANA BANTUAN OPERSIONAL SEKOLAH (BOS) TERHADAP MUTU SEKOLAH DI LINGKUNGAN DINAS PENDIDIKAN KOTA TASIKMALAYA - Fauzi, Hendra Lesmana (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
The government is obliged to increase socialization to the public about the importance of education for people's lives in today's modern era, and vice versa, the government is also obliged to maintain and improve the quality of education in order to obtain human resources who can compete in this era of globalization. One of the efforts to improve the quality of education includes striving for infrastructure in the school environment so that it can support teaching and learning activities that are conducive to the direction of competent and professional teachers, for this reason the School Operational Assistance (BOS) fund is a government policy which is aimed at completing the program. compulsory education with quality education. This research was motivated by a decrease in the number of students and a decline in the quality of education when viewed from the results of the national SD and SMP national examinations in the Tasikmalaya City Education Office. The study used a quantitative approach, with a sample of 69 respondents, the data from the questionnaire were analyzed using path analysis to find the magnitude of the influence of each dimension of the implementation of BOS funds on the quality of schools in SD and SMP Negeri in the Tasikmalaya City Education Office. Based on the research results, it was obtained data that the implementation of the BOS Fund Policy had a very strong influence on the quality of schools in SD and SMP Negeri Kota Tasikmalaya, with a contribution of 54.6%. The variable dimension of BOS Fund Policy Implementation which has the greatest influence on school quality is the resource dimension (26.19%), this means that to improve school quality, the most important thing is to increase the competence of stakeholder resources, including the managerial ability of the Principal teacher competence.